Developing Writing Materials for Students at the Eighth Grade of SMP N 3 Jambi - Munawwaroh, Khidayatul; Silfia, Efa; Mega, Mega; Bryan, Christopher; Heriadi, Valdhieny Andhiera (Universitas Batanghari Jambi, 2025)
ABSTRACT The objectives of this study were: (1) to identify the learners’ needs for eighth-grade students of SMP N 3 Jambi, and (2) to develop appropriate materials for eighth-grade students of SMP N 3 Jambi. This was a Research and Development (R&D) study. The subjects of the study were the students in the eighth grade of SMP N 3 Jambi. The research procedures were adapted from Jolly and Bolitho’s model in Tomlinson (1998) with some modifications, consisting of conducting the need analysis, writing the course grid, developing the first draft, getting expert judgment, and evaluating the first draft, also revising the first draft of the materials. The instruments to collect the data were need analysis questionnaire and an expert judgment questionnaire. The data from the need analysis were analyzed quantitatively using frequency and percentage, then the results were used to develop the course grid. The data from the expert judgment were analyzed quantitatively through descriptive statistics while the suggestions were used to revise the first draft of the materials. The product of this research is a set of writing materials entitled “Guide for Writing” for students of the eighth grade of SMP N 3 Jambi. The writing materials consist of three units, “My Best Friend”, “My Unforgettable Experience”, and “My Favorite Story”. Each unit consists of Pre-writing, Drafting, Responding, and Editing tasks ranging from 15-17 tasks. Based on the research findings from the expert judgment, the whole aspects of the developed materials were 3.62 which was in the range of 3.25 < x ≤ 4 and can be categorized as “very good”.